Modelling carbon and economic dynamics in livestock systems in Tanzania - Chan, Derek; Bahta, Sirak T. (CGIAR System Organization, 2023)
Livestock production in Tanzania remains overwhelmingly traditional, especially for ruminants, while domestic demand remains very much for products produced in traditional value chains. However, there are opportunities for upgrading value chains, especially in manufacturing leather and expanding productivity for milk and meat. Given the high potential climate impact of these livestock activities, it is important to understand their carbon dynamics and emission impacts. In this study, we examine the productivity and value-added potential for livestock value chains based on extant research and develop a concept for modelling carbon dynamics to be integrated into an economic value chain model in a participative manner. This marks the first step in developing a model where scenarios can be developed and “what‑if” analyses can be conducted on potential value chain transformation scenarios.